Aplikasi Sistem Pendukung Keputusan Perekrutan Karywan berdasarkan Hasil Tes Rekrutmen dengan Metode Fuzzy AHP dan Profile Matching pada Konsultan Manajemen Sumberdaya Manusia CV.X - Josia Christian; Silvia Rostianingsih; Yulia Yulia (Universitas Kristen Petra, 2022)
CV X is a human resource management consulting company serving personnel management services such as recruitment, assessment, making company policies, and making employment agreements. So far, all business processes are still done manually including the employee recruitment process. Based on the existing problems, this research will create a Decision Support System for Employee Recruitment based on Recruitment Test Results with Fuzzy AHP and Profile Matching Methods. The system is expected to optimize the efficiency of the recruitment process at CV X Human Resource Management Consultant. The results show that the system can help calculate candidate rankings with an accuracy of 83.975% when compared to manual ranking results. In addition, the system can also help reduce the influence of assessor subjectivity on ranking results.